FORMULASI PERMEN DARI SARANG SEMUT ASAL KALIMANTAN SELATAN - Setiawati, Evy; Crisnaningtyas, Farida (Kementerian Perindustrian, 2013)
Ant plant (Myrmecodia sp) is one of the many forest products that has a lot of benefits. Active compounds in this plant has been proven to to have benefit for the body. The aim of this research was to obtain the formulation ant plant products that have some benefits. The research methodologies consist of ant plant processing, phytochemical testing, formulation making, candy making, product testing according to SNI and organoleptic testing. Based on the phytochemical testing, ant plant (Myrmecodia sp) contained active compounds such as saponin, alkaloid, tannin, phenolic, flavonoid, triterfenoid and glycoside. Based on organoleptic test, the most preferred for ant plant candy formulation were consist of sugar, glucose, honey and mint, and 25% of ant plant extract. Based on SNI 357.1:2008 about hard candy, the formulations of ant plant candy meet the requirements specified.Keywords: ant plant, extraction, active compounds, formulation, candy